PERAN KEPEMIMPINAN DAN IMPLEMENTASI SUPERVISI AKADEMIK DALAM PENINGKATAN MUTU PROSES PEMBELAJARAN - Nendah Ridha Jatnika (MADINASIKA, 2019)
The research aims to analyze descriptively about the principal's leadership, the implementation of academic supervision, and the quality of the learning process as well as to verify verbally the role of the principal's leadership and the implementation of academic supervision on the quality of the learning process both individually and collectively. The research method used is descriptive and verification. The population in this study is the teacher of elementary schools in North Sumedang Subdistrict, using cluster random sampling technique. Data sources in this study are primary data and secondary data with correlation and regression analysis techniques. Descriptive research results prove that the principal's leadership, implementation of academic supervision, and the quality of the learning process are in good condition, although there are some aspects that are still weak. Verification research results prove that the principal's leadership and the implementation of academic supervision have a significant role in the quality of the learning process both individually and collectively.